THE NAMIBIAN LABOUR DISPUTE RESOLUTION SYSTEM: SOME LESSONS FROM SOUTH AFRICA - Felix Musukubili; Adriaan van der Walt (Obiter, 2014)
In Namibia and South Africa respectively, there are social partners (social partners are the workers’ and employers’ organisations in terms of the ILO classification) with common and divergent short- and long-term interests. These divergent interests must be accommodated and reconciled and this process is the subject of labour law and industrial relations. However, the processes employed in Namibia and South Africa vary. The purpose of this comparative article is to highlight and explain the differences between and similarities of the two respective countries’ labour dispute-resolution systems. This comparative approach brings to bear two schools of thought, the first being the convergence school, and the second is the divergence school. The convergence school holds that the influence of industrialisation gradually brings the labour-relations systems of various countries closer to one another. The divergence school, on the other hand, maintains that labour relations are sub-systems of political systems and manifestations of prevailing social and economic conditions. Despite these perspectives above, it should not be taken for granted that systems and institutions are transplantable as it is argued that any attempt to do so may entail a wish of rejection. The reason for this view is premised on the basis that Namibia and South Africa are not identical; there are distinct differences in certain areas, such as economic development. However, the differences between the systems do not mean that Namibia cannot adopt solutions that have proved successful in South Africa or vice versa, and therefore a degree of transferability may be accepted.